Internal and External Determinants of Bank Syariah Indonesia Capital Gain during the Pandemic - Resi Ariyasa Qadri; Etty Murwaningsari (Center for Risk Management & Sustainability and RSF Press, 2023)
This paper seeks to confirm and explain the relationship between internal factors of stock-lagged return and trading volume and external factors of composite price on returns of Bank Syariah Indonesia or BRIS. We collect the daily financial data of BRIS stock, Indonesia composite index, gold price, exchange rate, and Bank of Indonesia's deposit rate from the Refinitiv database. We obtained 1,230 time-series data to be analyzed further by implementing time-series analyses. Our research shows that the autoregressive integrated moving average (1,1,0) is the best model for univariate and multivariate analysis. Our study finds that lagged return has a negative effect on the bank’s daily return while trading volume has a positive impact on daily return. Our research reveals that composite price has the same effect as trading volume on daily return. Investors, especially short-term traders, may use our findings to formulate a different strategy for dealing with the volatility of Bank Syariah Indonesia stock. Our research contributes to the investment field by developing a new measurement for predicting the bank’s return when conducting short-term trading.